The fine arts in America - Taylor, Joshua Charles, 1917- (Chicago : University of Chicago Press, 1979)
Shows the growing importance of art in society in America over three centuries.
Includes bibliographical references and index.
Booklist.
Young Adult.
Young Adult
Keywords: Art, American; Art -- United States; Art -- United States